The Role of Management in Administering Inclusive Education - Javokhirbek Yoqubjonov Karimjon o‘g‘li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Inclusive education is recognized as a vital tool for ensuring equality and social integration in modern education systems. This article analyzes the role of management in administering inclusive education based on the IMRAD methodology. The study explores the strategic, organizational, and social aspects of management in effectively implementing inclusive education in educational institutions. The findings highlight the critical importance of management in training qualified personnel, developing infrastructure, and fostering collaboration with society. The article concludes with practical recommendations for advancing inclusive education within Uzbekistan’s education system.